Orientalism Revisited: A Critique of Western Discourses of Non-Western Development through the Post-colonial, Subaltern and Marxist Frames - Alamu, Ibrahim; Emmanuel Olaolu Ololade (RADINKA JAYA UTAMA PUBLISHER, 2025)
This paper critically examines the intersection of Edward Said’s Orientalism and Western perceptions of development in Asia, the Middle East, and North Africa (MENA). Through a qualitative textual analysis of seminal literature on Orientalism and development studies, this research deconstructs the dominant discourses that perpetuate Western-centric views of development in these regions. Drawing on Said’s seminal work, Orientalism (1978), this study identifies and interrogates the power dynamics, stereotypes, as well as cultural essentialisms that underpin Western representations of development in Asia and MENA. This research employs a critical discourse analysis (CDA) approach to examine a corpus of texts, including academic articles, policy documents, and literary works, addressing the central arguments and key assumptions of Orientalism. The textual analysis focuses on narratives that reinforce Orientalist tropes, marginalize indigenous perspectives, and legitimize Western dominance in development discourse. By juxtaposing Western development narratives with counter-narratives, this study exposes the epistemological tensions and power asymmetries that shape development policies and perceptions. The findings of this study contribute to a nuanced understanding of the complex interplay between Orientalism and Western development perceptions, highlighting the need for decolonial and inclusive approaches to development.